2021
DOI: 10.1002/suco.202100232
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the use of glass fiber reinforced polymer reinforcement in hollow‐core circular concrete columns

Abstract: This paper presents the results of an experimental investigation on the behavior of glass fiber reinforced polymer (GFRP) bar-reinforced hollow-core (GFRP-HC) circular concrete specimens under concentric, 25 mm and 50 mm eccentric axial loading and four-point bending. The main parameters investigated include the type of reinforcing bars, pitch of the helices and loading conditions. The test matrix of this study consists of 12 specimens, among which nine specimens (850 mm high) were tested under concentric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that fiber reinforced polymer (FRP), such as aramid fiber reinforced polymer (AFRP), basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP), can significantly improve the load bearing and deformation capacity of damaged/ undamaged concrete structures. [1][2][3][4][5][6][7][8] To accurately predict the load bearing capacity of damaged concrete after FRP strengthening, many compressive strength models have been proposed. [9][10][11][12][13][14][15][16][17][18] Guo et al 19 found that a compressive strength model of FRP-confined undamaged concrete Discussion on this paper must be submitted within two months of the print publication.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that fiber reinforced polymer (FRP), such as aramid fiber reinforced polymer (AFRP), basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP), can significantly improve the load bearing and deformation capacity of damaged/ undamaged concrete structures. [1][2][3][4][5][6][7][8] To accurately predict the load bearing capacity of damaged concrete after FRP strengthening, many compressive strength models have been proposed. [9][10][11][12][13][14][15][16][17][18] Guo et al 19 found that a compressive strength model of FRP-confined undamaged concrete Discussion on this paper must be submitted within two months of the print publication.…”
Section: Introductionmentioning
confidence: 99%